2016
DOI: 10.1039/c5cc08479b
|View full text |Cite
|
Sign up to set email alerts
|

Optical signaling in biofluids: a nondenaturing photostable molecular probe for serum albumins

Abstract: The systematic investigation of the interaction of a new class of molecular materials with proteins through structure-optical signaling relationship studies has led to the development of efficient fluorescent probes that can detect and quantify serum albumins in biofluids without causing any denaturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…In comparison with other detection methods, fluorescent probes are favored because of advantages including a rapid, non-invasive, and sensitive response. Accordingly, several fluorescent probes have been reported using many different types of fluorophore such as tetraphenylethylene, squaraine dye, and indolium derivative, which is based on aggregation-induced emission (AIE), molecular rotor containing donor-π-acceptor (D-π-A) structured fluorophore, and self-assembled nanoparticles [22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. However, there remain some problems to be solved, such as the low sensitivity and selectivity toward HSA.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with other detection methods, fluorescent probes are favored because of advantages including a rapid, non-invasive, and sensitive response. Accordingly, several fluorescent probes have been reported using many different types of fluorophore such as tetraphenylethylene, squaraine dye, and indolium derivative, which is based on aggregation-induced emission (AIE), molecular rotor containing donor-π-acceptor (D-π-A) structured fluorophore, and self-assembled nanoparticles [22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. However, there remain some problems to be solved, such as the low sensitivity and selectivity toward HSA.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, colorimetric and far-red uorescent dual probes with favourable sensitivity, selectivity and costefficiency are in urgent demand for practical applications. 28,29 The mechanism of these uorescent probes for the selective detection of Ag + is that Ag + shows a high tendency to coordinate with so Lewis base such as sulfur containing ligand due to the so Lewis acid character. As a part of work for Ag + recognition, we designed a dicyanomethylene-4H-chromene-based uorescence probe (DCPS-1) for the selective detection of Ag + , this probe would form complex with Ag + , accompanied with color change and turn-off far-red emission (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…This fact was evident by the higher quantum yield of the dye at λ =454 nm in the presence of HSA ( Φ =0.18) as compared to that in its nanoaggregate form ( Φ =0.10). Furthermore, changes in the CD signals of the protein upon incubation with different amounts of compound 1 showed a perturbation in the α‐helical structure of the protein template (Figure c), which suggested that the probe molecule had become embedded in the α‐helices of subdomain IIA of HSA . FTIR analysis also revealed that stretching frequencies related to the α‐helices of the protein (amide I, OH, and NH bands) were affected during the interaction with compound 1 (see the Supporting Information, Figures S13 and S14) …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, changes in the CD signals of the protein upon incubation with different amounts of compound 1 showed ap erturbationi nt he a-helicals tructure of the protein template (Figure 5c), whichs uggested that the probe molecule had becomee mbedded in the a-helices of subdomainIIA of HSA. [55,56] FTIR analysisa lso revealed that stretching frequencies related to the a-helices of the protein (amide I, OH, and NH bands) were affected during the interaction with compound 1 (see the Supporting Information, Figures S13 and S14). [57,58] Because pH value had ap ronounced influence on the assembly behavior of compound 1,w ea lso investigated the effect of pH value on its albumin-sensing properties.…”
Section: Resultsmentioning
confidence: 99%